Encapsulation and controlled release formulations of 5-fluorouracil from natural Lycopodium clavatum spores - Mundargi, Raghavendra C. (2016)
Cost effective, uniform-size multiparticulate formulations of the chemotherapeutic agent 5-fluorouracil (5-FU) loaded in natural Lycopodium clavatum spores were developed by three different encapsulation techniques: passive, compression and vacuum loading. The surface morphology, and micromeritic properties of 5-FU spore formulations were characterized by scanning electron microscopy and dynamic image particle analysis, respectively. The encapsulation efficiency of spores by vacuum-assisted loading was higher (49%) compared to passive and compression loading techniques. The vacuum-loaded formulation was selected for further development with a Eudragit RS 100 (EUD) coating that enabled controlled 5-FU release in simulated gastric (pH 1.2) and intestinal (pH 7.4) conditions. The surface morphology analysis after EUD coating at two different EUD concentrations (2.5% w/v and 10% w/v) indicates that a thin, conformal layer of EUD was deposited on the spore surface. The in-vitro release of 5-FU from coated spores exhibited a slower release profile compared to uncoated spores, and was extended for up to 30 h in simulated gastrointestinal conditions. Collectively, the findings demonstrate that EUD coated 5-FU loaded natural L. clavatum spores provide a controlled release formulation that would aid treatment options against gastrointestinal cancer and other related maladies.